PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM MENGURANGI JUMLAH SISWA PUTUS SEKOLAH KOTA PAREPARE - Rian Safitriana (Journal AK-99, 2021)
This research aims to find out the total budget of School Operational Assistance (BOS) and the number of dropout students over the past 5 years and the relationship between the school operational assistance budget (BOS) in reducing or reducing the number of dropout students in Parepare City. The benefits of this research are scientific benefits and practical benefits. The scientific benefit is that the results of this study are expected to be the material of scientific studies in the accounting science of regional finance, especially the assessment in the field of Basic Education and the Budget of the School Operational Assistance Fund (BOS), and the practical benefits that this research results are expected to contribute advice to all parties, especially to the Local Government and Education Office. The research site was conducted at the Parepare City Education Office and the research period began from January to April 2019. This research uses data collection techniques such as observation, interview, and documentation. The type of data used is the type of data according to the source, namely primary data obtained directly from respondents and Secondary Data obtained from documents related to research problems. This research uses data sources of person, paper, and place. The method of analysis used is a method of quantitative analysis by decrypting the total budget of School Operational Assistance (BOS) and the number of dropout students in the last 5 years and to find out the relationship between the school operational assistance budget (BOS) and the level of dropout students. The results of this study show that the budget of School Operational Assistance (BOS) received in Parepare City fluctuates in value, in the sense that it is still up and down. This is because the amount of School Operational Assistance (BOS) funds given to schools is calculated based on the number of pupils / students in each school, so that the school operational assistance (BOS) funds received by each school are not the same or varied, then the coverage of poor family students based on the data of dropout students in Parepare City from 2015 to 2017 decreased from 50 students to 12 dropout students and from the results of the analysis used correlation coefficient analysis, showing a very low correlation.